The Effects of Corporate Governance Implementations on Financial Performance: An Evidence from Turkey - SÖNMEZ, Adem Ruhan; YILMAZ, Fatma (International Journal of Contemporary Economics and Administrative Sciences, 2022)
This study investigate the effects of corporate board and audit committee characteristics and ownership structures on financial performance of listed firms in Turkey. The study used system GMM analysis of data from 104 listed firms in Turkey from 2012 to 2019 to test how each corporate governance variable initiated by the SEC of Turkey contributed to firm performance. Data were extracted from the annual reports of listed companies. According to the results of the analysis, there has not been any correlation between business performance and the number of members in board, independent members rate, female members rate, the frequency of the board meetings, ownership concentration, the number of members in the audit committee and audit committee meetings. In the study, it is determined that there is a positive and significant relationship between the business firm performance and risk committee and the frequency of the risk committee meetings.